Plan estratégico de marketing para la empresa de producción de ladrillos “Ceramlago”, de la ciudad de Nueva Loja, provincia Sucumbíos - Morocho Ramírez, Maritza Elizabeth (2015)
The rationale for the development of any organization base is the availability of administrative tools which ensure applicability increasing your income and reducing your expenses resulting business benefits. That is why through this premise was undertaken in the Strategic Marketing Plan for the company's production of bricks CERAMLAGO, which has the general objective; Develop a strategic marketing plan that allows CERMLAGO lead the local, national and international markets using the marketing plan as tools that allow the company to spread its production and increase your sales. Briefly can synthesize the development of this research as follows: Research bears the general title "DEVELOPMENT OF A STRATEGIC MARKETING PLAN FOR THE COMPANY PRODUCTION OF BRICKS CERAMLAGO, CITY OF NEW Loja, PROVINCE SUCUMBÍOS" Remarkably, within the methodology used, resorted to the use of the following methods: historical, deductive, inductive, statistical and analytical; regarding techniques, using both the survey was required, as well as interview and observación. Secondly the analysis of external factors of the company was held; for this, the economic, technological, social-cultural-political and legal forces Porter, both directly and indirectly in the normal course of business, in this way were identified key opportunities and threats of this organization were analyzed, what which allowed us to build the matrix MEFE external factors, which yielded a result of 2.66. He then proceeded to perform the analysis of the internal factors of the organization under study, for which an interview was raised to the Manager of the company, and a series of surveys of both internal customers as well as external customers the company, the analysis performed on the responses could identify their main strengths and weaknesses, as well build the matrix MEFI internal factors, which yielded a result of 2.56. As a result of the FO (Fortresses Vs. Opportunities), FA (Strengths Vs. Threats), DO (v Weaknesses Opportunities) and DA (v Weaknesses Threats), crosses could be determined the following strategic objectives for CERAMLAGO, which in In turn, they came to constitute the solid foundation on which the development of this research was cemented. Develop an advertising slogan in order to efficiently promote the image of the company. Use Static advertising in public spaces. Implement a permanent training plan for employees of CERAMLAGO. Offering discounts to customers in certain seasons. Schedule an aggressive advertising. Following the conclusions of all research work where details each of the results obtained from the various sources of information collected, in which case the budget required for the implementation of operational plans is $ 6590.00 US dollars are presented; it is estimated that this investment will strengthen the company image in the market and this improve profitability. To conclude this paper, we present a series of recommendations which are properly synthesized in an extract of the present investigation